Comparative efficacy and safety of transurethral laser surgery with holmium laser, KTP laser, 2-micron laser or thulium laser for the treatment of non-muscle invasive bladder carcinoma: a protocol of network meta-analysis - Jinfeng Yu; Junbiao Zheng (BMJ Open)
Introduction The potential of transurethral laser surgery in treating non-muscle invasive bladder cancer (NMIBC) has been confirmed, however which types of lasers may be preferentially prescribed remains a debate. The aim of this network meta-analysis is to investigate the comparative efficacy and safety of transurethral laser surgery with four common types of laser including holmium laser, potassium titanylphosphate (KTP) laser, 2-micron laser or thulium laser for the treatment of NMIBC.Methods and analysis A systematic search will be conducted to search all potentially eligible randomised controlled trials comparing different transurethral laser surgeries with each other or with standard transurethral resection among patients with NMIBC in PubMed, Embase, the Cochrane library, China National Knowledge Infrastructure, Wanfang database and Chongqing VIP from their inception until 31 May 2021. Two reviewers will be asked to independently select eligible studies, and assess the risk of bias of individual study with Cochrane risk of bias assessment tool. A random-effects network meta-analysis based on Markov chain Monte Carlo method will be carried out. Ranking probabilities will be considered to rank all laser types. Quantitative analysis will be carried out by using WinBUGS V.1.4.3.Ethics and dissemination Ethical approval is not required because this is a network meta-analysis of published data. We will submit all findings to some conferences for preliminary communication and to a peer-reviewed journal for publication.Trial registration number 10.17605/OSF.IO/TD9MW.